An analysis of the evolution of multidimensional poverty among children and adolescents in Uruguay between 2006 and 2014 - Colacce, Maira; Tenenbaum, Victoria (Estudios Económicos de El Colegio de México, 2017)
Based on the methodology proposed by Alkire and Foster, the objective of this paper is to estimate a multidimensional poverty index for children in Uruguay between 2006 and 2014. This allows the analysis of the reactions of non-monetary dimensions of wellbeing, in the context of an important increase of household income. The main results show a smaller reduction of the index compared to the monetary poverty, and stagnation in the last two years. This trend is largely explained by the dimensions of comfort and education.